Pertumbuhan dan Hasil Tanaman Kangkung (Ipomoea reptans Poir.) Akibat Pemberian Dosis Pupuk Urea dan Cara Pemberian yang Berbeda - Mila Sa'diyah Rohmah; Mahayu Woro Lestari; Anis Sholihah (Folium : Jurnal Ilmu Pertanian, 2023)
It is necessary to increase the production of water spinach in Malang City because it has decreased. One way to do this is to apply urea fertilizer because it contains a lot of N elements, so it is good for the growth process of kale because it is harvested during the vegetative period. The purpose of this study was to find out the appropriate dose of urea fertilizer and how to apply the appropriate urea fertilizer to the growth and yield of watercress plants. This research was conducted in the research area of ​​the Islamic University of Malang. The study used a factorial randomized block design (RAK) with control. The first factor was the dose of urea fertilizer: D1 = 50 kg/ha, D2 = 100 kg/ha, and D3 = 150 kg/ha. The second factor was the method of administration: C_1 = by immersion and C_2 = by dilution and control = without urea fertilizer. The observed data were analyzed for variance (F test) and continued with the 5% BNJ test. To find out the optimal dose, a regression test was carried out. The results showed that there was an interaction with the combination of 150 kg/ha fertilizer dose by pouring (D3C2) with a plant height of 32.06 cm. A Fertilizer dose of 50 kg/ha by immersion method (D1C1) gave the best effect on total plant fresh weight (106.08 g) and total plant dry weight (19.43 g). Giving a dose of 100 kg/ha increased the total fresh weight of plants with a weight of 107.62 g. Based on the results of the regression test, the optimum dose of urea fertilizer was 97.05 kg/ha. The addition of urea fertilizer using by immersion method increased the leaf area index (4.30) and stover dry weight (7.44 g).